2017
DOI: 10.3892/ijo.2017.4090
|View full text |Cite
|
Sign up to set email alerts
|

PRL-3 improves colorectal cancer cell proliferation and invasion through IL-8 mediated glycolysis metabolism

Abstract: Phosphatase of regenerating liver-3 (PRL-3) has been found to be overexpressed in liver metastases of colorectal cancer and rarely expressed in primary tumors, which plays an important role in the metastasis of colorectal cancer cells. Metabolism reprogramming has been found to be a hallmark of cancer cells, and aerobic glycolysis is a metabolic adaption for cancer cells and promotes cell proliferation. However, the association between PRL-3 and glycolysis in colorectal cancer cells is not well understood. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 34 publications
(35 reference statements)
4
24
0
Order By: Relevance
“…This indicates that PTP4A3 was related to the inhibition of cell proliferation caused by 1,4-BQ. The results agree with previous reports that PTP4A3 was involved in cell proliferation [28,29].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This indicates that PTP4A3 was related to the inhibition of cell proliferation caused by 1,4-BQ. The results agree with previous reports that PTP4A3 was involved in cell proliferation [28,29].…”
Section: Discussionsupporting
confidence: 93%
“…A gentle growing rate of ROS was observed in K562-PTP4A3 − cells, while a sharp increase was seen in K562-NC cells after the treatment of 20 µM 1,4-BQ. Overexpression of PTP4A3 was found to reduce the intercellular ROS level in colorectal cancer cells [28]. Further investigations are needed to explain the relationship between PTP4A3 and ROS.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…PRL-3-It was reported that when colorectal cancer cells (LoVo cell line) overexpress, this phosphatase had an increase of glucose consumption and lactate production in comparison to LoVo cell line wild type. Accordingly, high amount of HK2, PKM2, and LDH were detected when PRL-3 is overexpressed [10]. Importantly, these authors also reported similar results when patient colorectal carcinoma samples were screened.…”
Section: Ptps and Warburg Effectsupporting
confidence: 59%
“…Hence, glucose consumption, lactate production and the ratio of ATP/ADP are usually deemed as the indexes of glycolysis (Liu et al 2016). In addition, a number of enzymes are involved in the glycolysis process, including HK2, GLUT1, LDHA, and so on (Wan et al 2017;Xu et al 2017). During the current report, MALAT1 knockdown decreased the glucose consumption, lactate production, and ratio of ATP/ ADP, as well as the down-regulation of HK2 and GLUT1 levels, suggesting MALAT1 generated a promoted effect on glycolysis process.…”
Section: Discussionmentioning
confidence: 99%